#TITLE_ALTERNATIVE# - NIZAMI (NIM : 12212098), MUHAMMAD
Namora-I-Langit geothermal field is located in the Sarulla contract block in Tapanuli Utara District, North Sumatera Province in Indonesia. Geothermal system in Namora-I-Langit is liquid dominated and reservoir depth commonly below mean sea level with maximum reservoir temperature is 277oC. Fumarole is the mainly geothermal surface manifestation in the field. In Namora-I-Langit geothermal field, will be developed geothermal power plant with has capacity until 220 MWe and it is part of Sarulla 330 MWe Geothermal Project during 30 yearsÃ‚Â’ contracts. In Namora-I-Langit geothermal field, was undertaken exploration phase including geological, geochemistry and geophysical survey and also was drilled four exploration wells to collect any information from the subsurface. Development of numerical model of natural state uses information from conceptual model that is generated based on geological, geophysical, geochemistry and well data. The numerical model is built by using TOUGH2 software. The objective of this study are following: To develop numerical model of Namora-I-Langit Geothermal Field which achieve natural state condition with validate pressure and temperature profile of the model with measured data from 4 wells i.e. NIL 1-1, NIL 2-1, NIL 2-2 and NIL 3-1, to characterize reservoir that including area, thickness, pressure, temperature, permeability distribution and to determine geothermal energy reserve of numerical model of Namora-I-Langit Geothermal Field by probabilistic method. This is first numerical model of natural state that has been successfully developed.